Autopilot design for the ERICA tilt-rotorcraft - Sollazzo, A.; Luigi Federico, L.; Poderico, M. (My University, 2019)
The paper discusses the design of a full Autopilot for the ERICA tiltrotor. The structure of the whole control system is implemented by means of classic control technique. The Autopilot envisages several automatic modes, such as the typical hold modes as well as a trajectory following control mode. Both the activation logics of the Autopilot and the automatic nacelle positioning system for the flight envelope protection are also described. The whole control system is implemented in the FLIGHTLAB software environment and it is tested by means of a proper test campaign, whose most significant test simulations results are reported.